HIV-infected individuals with the CCR delta32/CCR5 genotype have lower HIV RNA levels and higher CD4 cell counts in the early years of the infection than do patients with the wild type. Copenhagen AIDS Cohort Study Group. - Katzenstein, T; Eugen-Olsen, J; Hofmann, B; Benfield, T; Pedersen, C; Iversen, A; Sørensen, A; Garred, P; Koppelhus, U; Svejgaard, A; Gerstoft, J (1997)
The relations among serum HIV RNA levels, CD4 cell counts, presence of the mutant CCR5-allele in heterozygous form, and clinical outcome was analyzed in 96 patients from the Copenhagen AIDS Cohort. In the early years of the infection, patients with the CCR5 delta32/CCR5 genotype had significantly lower HIV RNA levels (p = 0.005) and higher CD4 cell counts (p < 0.005) than did patients homozygous for the normal allele. The long-term clinical benefit of being heterozygous is small and cannot solely explain the large interpatient variation in progression rates. The beneficial effect of being heterozygous seems to be mediated by events in the early stages of the HIV infection.